Correction: Cobalt ion-coordinated self-assembly synthesis of nitrogen-doped ordered mesoporous carbon nanosheets for efficiently catalyzing oxygen reduction. Issue 43 (30th October 2017) - Wang, Haitao; Wang, Wei; Asif, Muhammad; Yu, Yang; Wang, Zhengyun; Wang, Junlei; Liu, Hongfang; Xiao, Junwu
Abstract : Correction for 'Cobalt ion-coordinated self-assembly synthesis of nitrogen-doped ordered mesoporous carbon nanosheets for efficiently catalyzing oxygen reduction' by Haitao Wang, et al., Nanoscale, 2017, 9, 15534–15541.